Choosing the right inhaler for your asthma or COPD patient - Usmani OS (Dove Medical Press, 2019)
Omar S Usmani National Heart and Lung Institute (NHLI), Imperial College London and Royal Brompton Hospital, Airways Disease Section, London, UK Abstract: Appropriate selection and correct use of inhalation devices is an integral component in the management of asthma and chronic obstructive pulmonary disease (COPD). It is well known that there are many challenges with the use of inhalers, and no one device suits all patients. Challenges can range from difficulties related to lung disease severity and pulmonary function to physical considerations, including manual dexterity and comorbidities such as arthritis. In terms of device selection and adherence, patient engagement and satisfaction are also important factors to consider. Furthermore, problems with inhaler use can be most evident in children and older patients. Here, we discuss aspects for consideration with commonly used devices, including nebulizers, pressurized metered-dose inhalers, dry powder inhalers, and the soft mist inhaler. As each inhaler offers varying technical properties, a tailored and personalized approach to the selection of the most appropriate device for the patient is highly recommended in order to increase the likelihood of achieving improved disease outcomes and enhance persistence with device adherence. Importantly, education and support is crucial, not only to enable patients to recognize the need for optimal disease management, but also to help them develop good inhaler technique. In addition, health care professionals should also aim to increase their knowledge of the devices they prescribe, and develop systems to ensure that they offer comprehensive support to patients in clinical practice. Considering these aspects, this review discusses potential strategies to help address the challenges of inhaler use in asthma and COPD. Keywords: inhaler, asthma, COPD, adherence